2007
DOI: 10.1111/j.1751-7915.2007.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial decolorization of textile dyes is an extracellular process requiring a multicomponent electron transfer pathway

Abstract: SummaryMany studies have reported microorganisms as efficient biocatalysts for colour removal of dye‐containing industrial wastewaters. We present the first comprehensive study to identify all molecular components involved in decolorization by bacterial cells. Mutants from the model organism Shewanella oneidensis MR‐1, generated by random transposon and targeted insertional mutagenesis, were screened for defects in decolorization of an oxazine and diazo dye. We demonstrate that decolorization is an extracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 60 publications
2
42
0
Order By: Relevance
“…Similar results were obtained in the study of an azoR homolog from Shewanella oneidensis (6). In conclusion, the well-studied azoreductase AzoR has no contribution to dye reduction in vivo and is actually a quinone reductase playing a role in protection against thiol-specific stress.…”
Section: Discussionsupporting
confidence: 74%
“…Similar results were obtained in the study of an azoR homolog from Shewanella oneidensis (6). In conclusion, the well-studied azoreductase AzoR has no contribution to dye reduction in vivo and is actually a quinone reductase playing a role in protection against thiol-specific stress.…”
Section: Discussionsupporting
confidence: 74%
“…This implies that the dye decolorization process is mainly dependent on oxygen concentration, not on microbial biomass. Similarly, the process is also very much dependent on the availability and nature of electron donors (Brige et al, 2008;Hong et al, 2008;Modi et al, 2010). Most of the anaerobic reduction processes are location specific but can take place both in cytoplasmic and membrane fractions isolated from bacterial cells (Kudlich et al, 1997).…”
Section: Sphingomonas Paucimobilismentioning
confidence: 99%
“…This hypothesis is supported by the findings that microbial excreted or artificial redox mediators catalyze the dye decolorization process [105,106,108]. [81] (continued) Recently, Brigé et al [109] demonstrated that dye decolorization is an extracellular reduction process requiring a multicomponent electron transfer pathway that consists of cytoplasmic membrane, periplasmic, and outer membrane components. Similarly, we have demonstrated the ability of bacteria to remove the color of azo dyes from solid agar medium, which suggested the accumulation of redox active enzymes or biochemical substances that were released into the medium during growth of the bacterial cells [40].…”
Section: Redox Control Of the Degradation Processmentioning
confidence: 87%